Crystallization of glasses - When to use the Johnson-Mehl-Avrami kinetics? - Svoboda, Roman (Elsevier Science, 2021)
Applicability of the Johnson-Mehl-Avrami (JMA) model was tested based on the universal criterion of the kinetic peak asymmetry. Theoretical simulations were used to prepare variety of kinetic peaks with different asymmetries, which were described by the JMA model and the masterplot function z(alpha). Based on the correlation between the simulated crystallization peaks and the JMA description, the following intervals of the degrees of conversion corresponding to the z(alpha) function maxima can be attributed to the respective values of the correlation coefficients: alpha(max,z) = 0.620 - 0.665 corresponds to the better correlation with the JMA model than r(2) = 0.999; alpha(max,z) = 0.585 - 0.705 indicates the correlation better than r(2) = 0.995. These intervals are significantly more lenient than those proposed in the original derivation of the masterplot approach. Even at r(2) = 0.995 the fit by the JMA model provides very accurate kinetic predictions utilizable for preparation of glass-ceramics.
Krystalizace skel - Kdy použít Johnson-Mehl-Avrami kinetiku?
Keywords: JMA model applicability; theoretical simulation; kinetic prediction; JMA model; teoretická simulace; kinetická predikce